2017
DOI: 10.1103/physrevb.95.134413
|View full text |Cite
|
Sign up to set email alerts
|

Impact of anisotropy on antiferromagnet rotation in Heusler-type ferromagnet/antiferromagnet epitaxial bilayers

Abstract: We report the magnetotransport properties of ferromagnet (FM)/antiferromagnet (AFM) Fe2CrSi/Ru2MnGe epitaxial bilayers using current-in-plane configurations. Above the critical thickness of the Ru2MnGe layer to induce exchange bias, symmetric and asymmetric curves were observed in response to the direction of FM magnetocrystalline anisotropy. Because each magnetoresistance curve showed full and partial AFM rotation, the magnetoresistance curves imply the impact of the Fe2CrSi magnetocrystalline anisotropy to g… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…The Néel temperatures of Cu-MNN and MNN are observed at 190 K and 250 K, while that of MGN is higher than 300 K, of which values are consistent from previous report 22,44,47,48 . Although H c and H ex show small variations by the MAN layer, no significant exchange-spring effects, such as an enhanced H c and rotation-direction dependence of AMR [23][24][25] , are observed in each MAN/CFN biayers. Besides, the resistivity of each MAN singlelayer film at T = 4 K is similar at approximately 0.14 -0.18 mΩcm.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The Néel temperatures of Cu-MNN and MNN are observed at 190 K and 250 K, while that of MGN is higher than 300 K, of which values are consistent from previous report 22,44,47,48 . Although H c and H ex show small variations by the MAN layer, no significant exchange-spring effects, such as an enhanced H c and rotation-direction dependence of AMR [23][24][25] , are observed in each MAN/CFN biayers. Besides, the resistivity of each MAN singlelayer film at T = 4 K is similar at approximately 0.14 -0.18 mΩcm.…”
Section: Resultsmentioning
confidence: 80%
“…The torque efficiency increases with divergent behaviors due to negative exchange interactions towards the compensation points 18,19 . On the other hand, in AFM, there are few systematical studies due to the difficulty of reading out the AFM Néel vector electrically as only a few AFM materials exhibit large electrical signals as an anomalous Hall effect [20][21][22] and anisotropic magnetoresistance [23][24][25][26] .…”
Section: Introductionmentioning
confidence: 99%
“…Relying on exchangebias coupling (Sec. I.C.3) between a Fe 2 CrSi ferromagnet and a Ru 2 MnGe antiferromagnetic Heusler alloy, Hajiri et al (2017) demonstrated the angular dependence of the in-current resistance on the direction of magnetic moments in plane geometry. The result was some combination of anisotropic magnetoresistance in both layers, since the ferromagnetic layer alone shows only a fraction of the magnetoresistance of the whole system.…”
Section: A Anisotropic Magnetoresistancementioning
confidence: 99%
“…They have recently attracted a renewed attention thanks to the high dynamical magnetization frequencies of AFs, enabling applications in fast interconversion and transmission of spin signals [3], and THz optics [4]. Additionally, vanishing magnetization of AFs can enable enhanced spin-transfer efficiency in electronic manipulation of the magnetic states for ultrahigh-density information storage, avoiding the constraints imposed by the angular momentum conservation and the dipolar fields ubiquitous to ferromagnetic systems [5].A number of novel phenomena have been recently observed or predicted for thin AF films, including antiferromagnetic spin-orbit torques [6][7][8], AF magnetoresistance [9], enhanced interconversion between electron spin current and spin waves [3,10], generation of THz signals [4,11], AF exchange springs [12,13], and topological effects [14][15][16]. While some of these phenomena are expected even for standalone AFs, strong exchange coupling at AF/F interfaces provides one of the most efficient approaches to controlling and analyzing the magnetization states of AFs, with the state of F controlled by the magnetic field or spin current, and characterized by the magnetoelectronic or optical techniques.…”
mentioning
confidence: 99%
“…A number of novel phenomena have been recently observed or predicted for thin AF films, including antiferromagnetic spin-orbit torques [6][7][8], AF magnetoresistance [9], enhanced interconversion between electron spin current and spin waves [3,10], generation of THz signals [4,11], AF exchange springs [12,13], and topological effects [14][15][16]. While some of these phenomena are expected even for standalone AFs, strong exchange coupling at AF/F interfaces provides one of the most efficient approaches to controlling and analyzing the magnetization states of AFs, with the state of F controlled by the magnetic field or spin current, and characterized by the magnetoelectronic or optical techniques.…”
mentioning
confidence: 99%